Food Security in Africa - Mahmoud, Barakat (IntechOpen, 2021)
This edited volume "Food Security in Africa" is a collection of reviewed and relevant research chapters offering a comprehensive overview of recent developments in the field of food safety and availability, water issues, farming and nutrition. The book comprises single chapters authored by various researchers and edited by an expert active in the public health and food security research area. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on Africa's food security challenges, quality of water, small-scale farming as well as economic and social challenges that this continent is facing. Hopefully, this volume will open new possible research paths for further novel developments.